De grano de oro a grano de cobre: los efectos de la Primera crisis de sobreproducción en la industria Cafetalera costarricense (1896-1910) - Montero Mora, Andrea (2011)
This article reconstructs the coffee crisis of the late nineteenth and early twentieth century. II takes into account the different trends and fluctuations of the business cycle in order to understand its impact on the national economy and those actors who made up the different stages of the coffee chain.